Time in the Novels Winning the International Prize for Arabic Fiction 2018-2020 - Hersh Mohammed Amin; Ihsan Burhanadden Ameen (QALAAI ZANIST JOURNAL, 2021)
This research, titled Time in the novels that won the International Prize for Arabic Fiction 2018-2020, studies Time from the narrative point of view, with its two types: natural and psychological. The focus is narrowed down to three novels that won the International Prize for Arabic Fiction, which are The Second Dog’s War by the Palestinian Ibrahim Nasrallah, The Night Post by the Lebanese Hoda Barakat, and The Spartan Diwan by the Algerian Abdel Wahab Issawi. The research includes theorizing Time narrative by illustrating from writings of specialists who are interested in narration. It, then, follows this with practical examples from the three narrations under study, in order to complete the picture of the narrative discourse consisting of both theoretical and practical dimensions. In addition to this, the researcher also seeks to extract the connotations envisaged by the novelists in their storytelling.